# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y^{2}-x -x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-2 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-3 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{2}-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{4}-6 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{5}+24 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a x y^{\prime }-b x y-c x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-x y-x^{2}-2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }-x y-x^{2}-4 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{3}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-x y-x^{3}-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{4}+3 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-x y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x^{3}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x^{6}+64 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y-x^{6}-x^{3}+42 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{4}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x^{2} y-x^{4}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y-x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x y-x^{2}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{2} y-x^{3}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{3} y-x^{4}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+c y^{\prime }+k y = 0
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = -\frac {1}{2}-\frac {\sqrt {1-12 w}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = 1
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = x
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = x
\] |
✓ |
✓ |
|
\[
{}5 x^{5} y^{\prime \prime \prime \prime }+4 x^{4} y^{\prime \prime \prime }+x^{2} y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = x
\] |
✗ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+x {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x^{2} \sin \left (\frac {y}{x}\right )^{2}+\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 8 \sqrt {x}\, \left (\ln \left (x \right )+1\right )
\] |
✓ |
✓ |
|
\[
{}v v^{\prime } = \frac {2 v^{2}}{r^{3}}+\frac {\lambda r}{3}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1+x
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+x +1
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{4}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \sin \left (x \right )
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \sin \left (x \right )+1
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x \sin \left (x \right )
\] |
✓ |
✓ |
|